O ensino de gramática da Língua Portuguesa a partir de uma proposta de sequência didática baseada no texto “O enigma do outro lado” de Stella Carr - Silva, Breno Pereira da (2023)
This dissertation presents the results of a research focused on Portuguese Language teaching for Elementary Education, especially on teaching grammatical aspects of this language. The mentioned research aimed particularly to propose, beyond prescriptive research, reflections on a reflexive approach to the understanding, by Elementary Education students, of contents related to Portuguese Language grammar. In this sense, one of the main results achieved by the study is the presentation of a pedagogical sequence through the text "O enigma do outro lado" (The Enigma from the Other Side), by Stella Carr, addressing text grammar. Another objective is to provide methodological support for the effective implementation of this approach. The study was based on theoretical reflections carried out by Perini (2000), Mattos and Silva (2004), Possenti (2012), and Neves (2013), since these authors discuss the teaching of Portuguese Language grammar in schools with significant approaches and methods. We also highlight the use of normative documents such as the Law of Guidelines and Bases of Education (LDB), the National Common Curriculum of Basic Education, the National Education Plan, the National Common Curricular Bases, among others, which guide the pedagogical practice of Brazilian education. Such documents establish guidelines, principles, and norms that guide the educational system, defining what should be taught, the learning objectives, the competencies, and the expected skills of students, among other important aspects that direct how teaching practice needs to happen effectively, such as the Law of Guidelines and Bases of National Education No. 9,394 (1996), the General National Curricular Guidelines of Basic Education (2013), the National Education Plan (2014), and the National Common Curricular Base (2017). The method employed will be a didactic sequence, related to pedagogical practice to meet the Research Line to which the research is linked to the Postgraduate Program in Letters and Linguistics of the Faculty of Letters of the Federal University of Goiás (PPGLL-FL-UFG), with a qualitative approach. This means that the study will follow a structured plan of educational activities and will be based on analysis and interpretation of qualitative data, seeking to understand more subjective and in-depth aspects related to the addressed theme. This methodological choice is common in educational research, which seeks to explore in a detailed and rich way a certain teachinglearning context.